The ontogeny of talo‐crural appositional articular morphology among catarrhine taxa: Adult shape reflects substrate use. Issue 3 (20th May 2014) - Turley, Kevin; Frost, Stephen R.
ABSTRACT The upper ankle joint forms a single articular plane between organism and the foot and substrate. Singular warp analysis shows that its shape reflects substrate use. This study explores whether the differences in shape are genetic with a developmental trajectory evident during ontogeny or epigenetic and the result of substrate use by the individual. A total of 418 matched distal tibial and proximal talar landmarked surfaces from adult and subadult specimens from 12 diverse catarrhine taxa were studied. Specimens were grouped by molar eruption (M1, M2, and M3) for comparative analysis. Generalized Procrustes analysis, multivariate regression, relative warp analysis, singular warp analysis, and permutation tests were used. Singular warp analysis for the entire cohort was highly significant in the first singular warp, with the adult taxa sorting by substrate use. All 173 subadults clustered with an adult "arboreal" shape profile. Among Hominoidea, adults (M3) sorted by substrate use with Pan paniscus and Hylobatidae assuming an "arboreal" shape separate from Pan troglodytes and the remaining taxa with "terrestrial" shape. Cercopithecoid adults sorted by substrate use as well, with the M3 specimens of Papio hamadryas and Macaca thibetana demonstrating a "terrestrial" shape. Differences in mode of locomotion did not affect the findings in the first singular warp. Results confirmed the convergence of talo‐crural shape among superfamilies based on substrate use and divergence in shape within Pan and Macaca, based on substrate use. The shape differences among adults (M3) are consistent with a plastic response to the behavioral stimulus of substrate use. Am J Phys Anthropol 154:447–458, 2014. © 2014 Wiley Periodicals, Inc.